Innovative Gastrointestinal Drug Delivery Systems: Nanoparticles, Hydrogels, and Microgrippers - Haiming Chen; Waliul Islam; Jessica El Halabi; Ling Li; Florin M. Selaru (Frontiers in Bioscience-Landmark)
Over the past decade, new technologies have emerged to increase intrinsic potency, enhance bioavailability, and improve targeted delivery of drugs. Most pharmaceutical formulations require multiple dosing due to their fast release and short elimination kinetics, increasing the risk of adverse events and patient non-compliance. Due to these limitations, enormous efforts have focused on developing drug delivery systems (DDSs) for sustained release and targeted delivery. Sustained release strategies began with pioneering research using silicone rubber embedding for small molecules and non-inflammatory polymer encapsulation for proteins or DNA. Subsequently, numerous DDSs have been developed as controlled-release formulations to deliver systemic or local therapeutics, such as small molecules, biologics, or live cells. In this review, we discuss the latest developments of DDSs, specifically nanoparticles, hydrogels, and microgrippers for the delivery of systemic or localized drugs to the gastrointestinal (GI) tract. We examine innovative DDS design and delivery strategies tailored to the GI tract’s unique characteristics, such as its extensive length and anatomical complexity, varying pH levels and enzymatic activity across different sections, and intrinsic peristalsis. We particularly emphasize those designed for the treatment of inflammatory bowel disease (IBD) with in vivo preclinical studies.